The United Kingdom's special responsibilities at the United Nations: Diplomatic practice in normative context. (May 2020) - Ralph, Jason; Gifkins, Jess; Jarvis, Samuel
In a 2017 speech to the United Nations, Theresa May referred to the United Kingdom's 'special responsibilities'. This article examines how the United Kingdom can properly discharge those responsibilities at the United Nations. We offer an innovative analytical framework that merges English School theory of international society with diplomatic practice theory, and find that there are limits to the claim that the United Kingdom compensates for its relative material decline through diplomatic activism. We identify the special responsibility of the permanent member in terms of a capacity to reconcile the 'concert' and 'governance' functions of the Council, and to contribute materially to the achievement of governance objectives in areas where consensus is possible. Drawing on extensive interview data, and illustrating with reference to current debates on peacekeeping, we find that a state's capacity to 'punch above its weight' diplomatically is linked to its material commitments and to a more inclusive approach in the Council.